Euphorbia helioscopia L.: A phytochemical and pharmacological overview. (April 2021) - Yang, Yan; Chen, Xufei; Luan, Fei; Wang, Min; Wang, Ze; Wang, Jiuling; He, Xirui
Abstract: Euphorbia helioscopia L. which is called " Zeqi " in China, is a medicinal plant extensively distributed worldwide, especially in China, and has been widely used for decades to treat various diseases including edema, phlegm and cough, malaria, dysentery, scab, tuberculous fistula, osteomyelitis, and cancer. The present review aims to provide up-to-date information on E. helioscopia, including its traditional uses, phytochemistry, quality control, pharmacological research, toxicology, and human studies in exploring future scientific and therapeutic potentials in disease treatment. So far, a total of 173 terpenoids, as well as polyphenols, steroids, lipids, and volatile oils have been isolated and identified from E. helioscopia. Among them, diterpenoids and ﬂavonoids are the most important and abundant bioactive constituents. Modern pharmacological studies have demonstrated that E. helioscopia has outstanding bioactivities especially on antiproliferative and multidrug resistance modulating. Nevertheless, most of these studies were carried out in vitro . The quality control, metabolites identification, in-depth in-vivo studies as well as toxicology and human studies for the crude extracts and active components are still very limited. Consequently, more well-designed pre-clinical and clinical studies are required to justify their reported therapeutic potential. Graphical abstract: Image 1 Highlights: The medicinal uses, phytochemistry, pharmacology, toxicology and clinical application of E. helioscopia are summarized. Terpenoids are the major chemical constituents of E. helioscopia. Biological activities and mechanism of both crude extract and isolates compounds are discussed in this review.